Analysis Of Calculation Of Illumination Needs At Tadulako University Hospital - Yudizthiranda; Agustinus Kali; Yusnaini Arifin (LPPM Universitas Tadulako, 2024)
Introduction: Lighting in the room varies, this is adjusted to the activities carried out in the room. Each room has its own lighting standards. The provision of electric power must meet sufficient capacity to serve the load. The construction of the Tadulako University College Hospital project cannot be separated from the need for electricity. In this building, electric power is used to meet lighting, air conditioning and medical needs. Method: This study uses a comparative analysis method to determine the suitability between the lighting calculation results and established standards, as well as a quantitative method in calculating lighting factors. Results and Disscussion: This study shows that the use of Downlight and LED Panel lamps at Tadulako University Hospital has met the standards of PERMENKES NO. 24 of 2016. Downlights are used in public spaces and corridors because they provide more focused and bright lighting, while LED Panels are used in special rooms for the comfort of patients and medical personnel. The trial showed that all rooms comply with the established lighting standards. Conclusion: This study concluded that the lighting system in Tadulako University Hospital using Downlight and LED Panel lamps has met the standards set by PERMENKES NO. 24 of 2016. LED Panel lamps are used in certain rooms to provide comfort for patients and medical personnel, while Downlight lamps are used in public rooms and corridors because the lighting is more focused and bright.